Accompanying the Development of Sidetapa‘s Fruit Brem as a Leading Tourism Product in Buleleng Regency - Widiastini, Ni Made Ary; Prayudi, Made Aristia; Rahmawati, Putu Indah; Dantes, Gede Rasben (Universitas Sebelas Maret, 2023)
This community service program was carried out to help fruit brem craftsmen in Sidetapa Village so that their products are more acceptable to the market. Sidetapa Village has been able to develop itself as a tourist destination. Visits from various parties, both tourists, elements of the government, and academics, positively impacted the development of tourism in the village. In its development, the people of Sidetapa Village were able to produce products to support tourism activities, and even became one of the superior products, namely brem made from local fruits using a fermentation technique. Brem is produced as a fermented drink with three flavors: honey wine, mangosteen rind, and mangosteen fruit. To make the product acceptable to the people, the producers of fruit brem in Sidetapa Village received assistance in product and market testing. Implementing this community service program consists of assisting in product sales analysis, product testing in the laboratory to determine the nutritional content of products and more informative packaging. Through product testing, Sidetapa’s fruit brem can provide information about the content of alcohol, sugar and carbohydrates per one bottle of drink. Meanwhile, through a market test, artisans can find out market tastes. It is hoped that through this assistance, fruit brem producers in Sidetapa Village can maintain their product production in terms of quality and quantity.Keywords: brem; fruit; product; Sidetapa; tourism